Transformasi Kesehatan Digital: Peran Teknologi Komputer - Retio Regah; Augustinus Robin Butarbutar (STIKES Columbia Asia Medan, 2024)
The advancement of computer technology has greatly impacted the healthcare industry, transforming the way healthcare services are delivered and managed. This article elucidates the role of computer technology in enhancing the quality of healthcare services through various innovations such as Electronic Medical Records (EMR), telemedicine, big data analytics, and artificial intelligence (AI). The implementation of these technologies has improved efficiency in healthcare service processes, enhanced diagnostic accuracy, expanded patient access to medical services, and enhanced overall patient information management. With a focus on leveraging computer technology, this article outlines its positive impact on the overall quality of healthcare services.